Magnetoelectric Plasma Preparation of Silicon-Carbon Nanocomposite as Anode Material for Lithium Ion Batteries - Fangfang Wang; Maochuan Gao; Ruoyu Hong; Xuesong Lu (Applied Sciences, 2020)
A high-performance silicon-carbon nanocomposite facilely prepared by one-step magnetoelectric plasma pyrolysis of the mixture of methane, silane, and hydrogen is proposed for lithium-ion batteries. The ratio of silane, methane, and hydrogen was studied to optimize the properties of the composite. When the ratio of hydrogen/silane/methane is 1:1:3, the composite is composed of spherical Si nanoparticles that uniformly attach to the surface of the tremelliform carbon nanosheets framework, in which the tremelliform carbon nanosheets can effectively resist the volumetric change of the Si nanoparticles during the cycles and serve as electronic channels. The silicon-carbon nanocomposite exhibits a high reversible capacity (1007 mAh g−1 after 50 cycles), a low charge transfer resistance, and an excellent rate performance. In addition, the proposed process for synthesizing silicon-carbon nanocomposite without expensive materials or toxic reagents is an environmentally friendly and cost-effective method for mass production.